Blighted hillsides after the 1906 earthquake. - Unknown:::Creator:::::::::::: (M. Rieder)
Written on recto: "A Reversion to wilderness. The blighted hillsides of San Francisco, after the Earthquake and Fire, San Francisco, April 18, 1906."